Influence of team success, fixture congestion and playing position on physical performance of elite youth soccer players during an international tournament - Kovács, B. M.; Malone, J.; Bognár, M.; Bali, P.; Pánics, G. (Journal of Human Sport & Exercise, 2021)
The purpose of the present study was to examine the influence of team success, fixture congestion and playing position on physical performance of elite youth soccer players during an international tournament. Physical match data was collected from 22 matches for U17 soccer players (n = 112) across 12 clubs during the play-off stage of the 2015-2016 Future Talents Cup International tournament. Match data was collected using a GPS device for physical performance measures across different positions, level of team success and during match congestion (MD1, MD 2 and MD3). The top ranked teams produced significantly higher total and low speed running distances compared to bottom ranked teams (p < .05). Players covered significantly more total distance and PlayerLoadTM on MD1 compared to MD2 and MD3 (p < .05). High speed distance output remained unaffected during this period of match congestion. Central defenders were found to have the lowest output across physical performance variables compared to all other positions (p < .05). Wide players (WD and WM) produced the greatest outputs at higher speed distances compared to other positions (p < .05). Therefore, the present study revealed that teams who had higher levels of success produced greater physical outputs compared to those of lower rankings. Match congestion resulted in a reduction in total and lower speed distances covered. Finally, differences in physical demands across playing positions was evident. Coaches should be aware of the implications of fatigue during periods of fixture congestion and the individual positional requirements for youth soccer players.